Enzyme Degradation Reagents Effectively Remove Mycotoxins Deoxynivalenol and Zearalenone from Pig and Poultry Artificial Digestive Juices - Tso, Ko-Hua; Ju, Jyh-Cherng; Fan, Yang-Kwang; Chiang, Hsin-I (Toxins, 2019)
Mycotoxin removers include enzymes and adsorbents that may be used in animal feeds to eliminate the toxic effects of mycotoxins. This study aimed to determine the removability of two different types of mycotoxin removers, adsorbents and enzyme degradation reagents (EDRs), in the simulated gastrointestinal conditions of pigs and poultry. Seven commercial mycotoxin removers, including five EDRs and two adsorbents, were tested in vitro. In this study, the supplemented dosages of mycotoxin removers used in pig and poultry feeds were the commercial recommendation ranging from 0.05% to 0.2%. For pigs, the in vitro gastric and small intestinal simulations were performed by immersing the mycotoxin-tainted feed in artificial gastric juice (AGJ) at pH 2.5 for 5 h or in artificial intestinal juice (AIJ) at pH 6.5 for 2 h to mimick in vivo conditions. For poultry, mycotoxin-tainted feeds were immersed in AGJ for 2 h at pH 4.5 and 0.5 h at pH of 2.5, respectively, to simulate crop/glandular stomach and gizzard conditions; the small intestinal simulation was in AIJ for 2 h at pH 6.5. For the pig, EDRs and adsorbents had deoxynivalenol (DON) removability (1 mg/kg) of 56% to 100% and 15% to 19%, respectively. Under the concentration of 0.5 mg/kg, the zearalenone (ZEN) removability by EDRs and adsorbents was 65% to 100% and 0% to 36%, respectively. For the simulation in poultry, the removability of DON by EDRs and adsorbents (5 mg/kg) was 56% to 79% and 1% to 36%, respectively; for the concentration of 0.5 mg/kg, the removability of ZEN by EDRs and adsorbents was 38% to 69% and 7% to 9%, respectively. These results suggest that EDRs are more effective in reducing DON and ZEN contamination compared to the adsorbent methods in the simulated gastrointestinal tracts of pig and poultry. The recoveries of DON and ZEN of pig in vitro gastrointestinal simulations were higher than 86.4% and 84.7%, respectively, with 88.8% and 85.9%, respectively, in poultry. These results demonstrated the stability and accuracy of our mycotoxin extraction process and in vitro simulation efficiency.